Neolignans from leaves of Ocotea catharinensis - Lordello, Ana Luísa Lacava; Yoshida, Massayoshi [UNESP] (Elsevier, 1997)
A hexane extract of Ocotea catharinensis leaves afforded, by chromatographic fractionation, 11 neolignans, eight of the benzofuran- type (including three new compounds) and three of the bicyclo[3.2.1] octane-type (including two new compounds).
Keywords: Bicyclo[3.2.1]octane neolignans; Hexahyclrobenzofuran neolignans; Lauraceae; Leaves; Ocotea catharinensis; benzofuran derivative; bicyclo[3.2.1]octane derivative; neolignan; chromatography; drug isolation; drug structure; nonhuman; plant leaf; proton nuclear magnetic resonance; tree